2003
DOI: 10.1097/00000542-200301000-00024
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Preemptive Analgesia on Pain and Cytokine Production in the Postoperative Period

Abstract: Proinflammatory cytokines are key mediators of illness symptoms, including hyperalgesia. The present results suggest that preemptive epidural analgesia is associated with reduced postoperative pain and attenuated production of proinflammatory cytokines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
86
0
7

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(99 citation statements)
references
References 13 publications
6
86
0
7
Order By: Relevance
“…Perioperative complications can lead to a modulation of the immune state, decrease in tumor surveillance, and possibly increased risk of disease recurrence and disease-specific death. [12][13][14][15] To the best of our knowledge, the current study is the first to examine the association between the occurrence of a postoperative complication and long-term outcomes among patients undergoing hepatic resection for ICC. The current study is important because the data have demonstrated that postoperative complications were independently associated with both RFS and OS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perioperative complications can lead to a modulation of the immune state, decrease in tumor surveillance, and possibly increased risk of disease recurrence and disease-specific death. [12][13][14][15] To the best of our knowledge, the current study is the first to examine the association between the occurrence of a postoperative complication and long-term outcomes among patients undergoing hepatic resection for ICC. The current study is important because the data have demonstrated that postoperative complications were independently associated with both RFS and OS.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14] In turn, perioperative complications may exacerbate this inflammatory response and induce a state of immunosuppression. 14 This state of immunosuppression may decrease tumor surveillance and lead to detrimental effects, including worse long-term oncological outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…17 The important role that inflammation plays in cancer and operative outcomes is being increasingly recognized. [18][19][20][21][22] Increased preoperative NLR may be an important indicator of the inflammatory state of patient at the time of surgery. This marker is easily obtained from a patient's routine preoperative laboratory studies and is easily calculated.…”
Section: Introductionmentioning
confidence: 99%
“…The mean value of serum IL-10 measured 1 h postoperatively increased significantly in both RAM and GAM group when compared with preoperative IL-10 with p<0.05. It shows there is a possibility of regional anesthesia anti-inflammatory effects due to blockade of C fibers, 7 thereby reducing the production of cytokines 8 and block the activity of the sympathetic nerve fibers. [9][10] Therefore, postoperative pain caused primarily by tissue inflammation and activation of C-fibers by reducing the production of cytokines that may limit the inflammatory response after surgery and postoperative pain severity.…”
Section: Discussionmentioning
confidence: 99%